PERCERAIAN KARENA LI’AN DAN AKIBAT HUKUM DALAM PERSPEKTIF FIQIH ISLAM DAN KOMPILASI HUKUM ISLAM - ZAISIKA KHAIRUNNISAK (PREMISE LAW JURNAL, 2015)
Li’an is a specific statement used by a husband for accusing his wife of committing adultery so that he has the reason to reject the child who is delivered by her. that the procedure of divorce because of li’an, according to the Islamic Fiqh, was when a husband swore on oath four times, saying that he said the truth in his accusation. In his fifth oath, he said that he would be cursed by Allah if he told a lie. His wife also swore on oath four times, saying that she did not commit any adultery. In her fifth oath, she said that she would be cursed by Allah if her husband was right. Both of them then did li’an in front of the people who had the same faith. Article 127 of KHI points out that li’an will be valid when it is done before the Religious Court. The legal consequence of li’an in the Islamic Fiqh and in KHI has one similarity, that is, third and final divorce, while in the Islamic Fiqh it still has some other legal consequences. Legal protection for a woman who is done the li’an by her husband, according to the Islamic law, will get the right to have the whole dowry from him, and in KHI she has the right on the joint property and she restores her good name by swearing on oath for response. A mula’anah child has the same position as an illegitimate child in which he did not have any right to inherit from his father who has done the li’an to his mother. KHI points out that there is no prohibition for mula’anah child to receive a gift or a will from his father who has done a li’an to his mother. A mula’anah child has the right to get protection, based on Article 23 of Law No. 23/2002 and receives his rights as a child. Keywords: Li’an, Procedure of Li’an Divorce, Mula’anah Child